Anzac Civil Religion? A Survey of the Australian Public on Their Interaction with Anzac - Fallon, Breann (Journal for the academic study of religion, 2017)
It is often argued that Anzac is the national civil religion of Australia. Existing research is based largely in cultural evidence sourced from memorials, services, newspapers, advertising, theatre, political speeches, attendance numbers, and public policy. In this article, survey data gathered in New South Wales is presented in order to provide an additional perspective on the interactions between Australians and Anzac. From this particular set of data, four narratives of Anzac interaction are identified: the 'traditional' narrative, the 'carnivalesque' narrative, the 'passive participation' narrative, and the 'anti-Anzac' narrative. These narratives are analysed via a hybridised methodology employing the work of Robert N. Bellah (1988) on civil religion and Paul Tillich (1957) on ultimacy. This methodology analyses each narrative to identify a worship paradigm (if present) and the effect of the worship paradigm on individual ultimacy. Some of the four narratives adhere to the typology of civil religion, while others do not. The four narratives of this particular survey cohort display a varied interaction with Anzac. Anzac is both a point of sacrality and secularity, of inclusion and exclusion, with many of the feelings and experiences reported by respondents insufficiently described in existing research. While this survey does not pretend to be exhaustive or provide conclusive answers, it does provide a first look at what lies beneath the surface in the study of Anzac as a sacral entity.